A stable home for an equine pathogen: valid publication of the binomial Prescottella equi gen. nov., comb. nov., and reclassification of four rhodococcal species into the genus Prescottella. Issue 9 (14th September 2022) - Sangal, Vartul; Goodfellow, Michael; Jones, Amanda L.; Sutcliffe, Iain C.
Abstract : Opinion 106 of the Judicial Commission has clarified the nomenclature of the taxon variously named Rhodococcus equi, 'Prescottella equi ' and Rhodococcus hoagii . As a consequence, we present here the genus name Prescottella and that of its nomenclatural type species, Prescottella equi comb. nov., for valid publication and propose the reclassification of four rhodococcal species as novel combinations in the genus, namely Prescottella agglutinans Guo et al. 2015 comb. nov., Prescottella defluvii Kämpfer et al . 2014 comb. nov., Prescottella soli Li et al . 2015 comb. nov. and Prescottella subtropica Lee et al . 2019 comb. nov. In addition, we note that a clinical isolate, strain 86–07 (=W8901), likely represents an additional species within the genus Prescottella . Nearly a century after the original description of the type strain of the type species as Corynebacterium equi, we provide a stable home for Prescottella equi and its relatives.